Antecedents Service Quality at Mother and Child Hospital in Purwakarta - Hanoum, Farah Chalida; Rizan, Mohamad; Handaru, Agung Wahyu (Jurnal Maksipreneur, 2023)
Health-supporting equipment and infrastructure affect how well medical services are delivered in hospitals. Other resources cannot replace human resources in an organization. This shows that the success of a hospital's health services depends on the quality of the health workers owned by the hospital. Research on the topic of service quality with the addition of the independent variables of work-life balance and job satisfaction in health workers with a background in the health sector is still rare in Purwakarta Mother and Child Hospital, where the existing literature has not been explained. This study was to determine the effect of work-life balance, job satisfaction, and work-life balance and job satisfaction on the quality of care for nurses. The sample in this study was 200 female nurses at the Purwakarta Mother and Child Hospital. The hypothesis was tested by structural equation modeling (SEM) with Lisrel 88.0 software. The result of the research is that job satisfaction has a significant effect on service quality. Work-life balance and job satisfaction have an important role in determining the improvement of the quality of nurse services at the Mother and Child Hospital in Purwakarta, West Java Province. This research study implies that hospitals can improve the work-life balance and job satisfaction experienced by nurses at the Mother and Child Hospital in Purwakarta, West Java Province, so that the quality of nurse services can continue to improve.